Pergolakan Inisiator dan Tawaran Metode Takhrij Hadis antara Ahmad Al-Ghumari dan Mahmud Al-Tahhan - Yaqin, Aennul (Tahdis: Jurnal Kajian Ilmu Al-Hadis, 2022)
This article discusses the debate around who pioneered the takhrij hadith method. The figure in dispute is between Aḥmad al-Ghumārī and Maḥmūd al-Ṭaḥḥān. In addition, this article also discusses the method of takhrij hadith offered by the two. The results of this article show that the pioneer of the takhrij hadith method is Aḥmad al-Ghumārī. Although Maḥmūd al-Ṭaḥḥān claims to have not found any figures who have written about the takhrij hadith method. Regarding their offer of takhrij method, Aḥmad al-Ghumārī presents his offer in two ways, while Maḥmūd al-Ṭaḥḥān presents it in five ways. Keywords: Hadith, Takhrij, Ahmad al-Ghumārī, Maḥmūd al-Ṭaḥḥān